Real estate appraisal terminology - Boyce, Byrl N.; American Institute of Real Estate Appraisers; Society of Real Estate Appraisers (Cambridge, Mass. : Ballinger Pub. Co., 1984)
The revised edition of this book was based on the change that had occurred in the profession and criticism on the existing terms and definitions by users. Much of this revision was directed towards refinement of existing terms and to broaden terms in the areas of finance, statistics and energy.
At head of title: American Institute of Real Estate Appraisers, Society of Real Estate Appraisers.
Includes bibliographical references: p. 355-367.
usc 22/09/2017
Loans
Keywords: Real property